The Impact of Perception and Fear on the Adoption of Protective Measures Against COVID-19: A Mediation Analysis - Ali Kılınç; Alaettin Ünsal; Didem Arslantaş (Scientific Reports in Medicine, 2026)
Objective: COVID-19 has had physical, mental, and social impacts worldwide, yet uptake of protective behaviors varied. We aimed to assess how COVID-19 disease perception and fear relate to adoption of precautions among adults in Türkiye. Methods: After ethics approval, we conducted a cross-sectional online survey in Türkiye (March 1–April 1, 2021) using researcher networks for recruitment. Measures included the COVID-19 Disease Perception Scale (dangerousness and contagiousness) and the Fear of COVID-19 Scale. Adherence to COVID-19 precautions (ACP) was self-reported and scored as the number of preventive measures adopted (0–11). Results: Of 4,477 responses, 4,011 participants were included after removing duplicates and incomplete entries (56.4% female; n=2,261). Mean (SD) ACP score was 5.99 (2.25) (median 6.0). Adherence was higher among females; those with a university degree; married participants; those not living in a separated/divorced family structure; those reporting good income; participants with chronic disease; non-smokers and non-drinkers; and those reporting a COVID-19 related death in their family or close social circle. Higher perceived contagiousness was associated with greater adoption of preventive measures, with perceived dangerousness and fear mediating this relationship. Conclusion: Public health efforts that strengthen accurate perceptions of infectious disease dangerousness and contagiousness, and address related fear, may increase use of protective measures and help reduce transmission in future pandemics.